2021
DOI: 10.1016/j.afjem.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of urological emergencies and surgical interventions in a single tertiary health center

Abstract: Objectives Emergency urologic conditions are relatively common, albeit rarely life threatening, there is often a need for prompt and expedient management in order to avert severe or permanent morbidities. This study aimed to evaluate the spectrum of Urologic emergencies and interventions offered in a tertiary hospital in Nigeria. Patients and methods We retrospectively reviewed the records of patients who were managed in our institution for emergency urologic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…A retrospective study conducted in Ahmadu Bello University Teaching Hospital have reported that urinary retention was the most common urological emergency noted over a 6-year period, 352 out of 681 urological emergencies and 41.9% of the patients proceeded to have suprapubic catheter (SPC) following failed urethral catheterization. Several different approaches have been described by literature to achieve transurethral catheterization for patients with DUC; however, many of the basic requirements to achieve this are not readily available to us or expensive to procure 3 . Although the practice of open suprapubic catheterization has given way to percutaneous suprapubic catheterization, either with or without image guidance, our patients remain apprehensive and reluctant about the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted in Ahmadu Bello University Teaching Hospital have reported that urinary retention was the most common urological emergency noted over a 6-year period, 352 out of 681 urological emergencies and 41.9% of the patients proceeded to have suprapubic catheter (SPC) following failed urethral catheterization. Several different approaches have been described by literature to achieve transurethral catheterization for patients with DUC; however, many of the basic requirements to achieve this are not readily available to us or expensive to procure 3 . Although the practice of open suprapubic catheterization has given way to percutaneous suprapubic catheterization, either with or without image guidance, our patients remain apprehensive and reluctant about the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Western countries [13]. A total of 5 patients were treated during the study period, priapism represents 0.9% of all urological emergencies seen.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency services are some of the most important functions of any hospital and they cut across all specialties [6]. Urological emergencies are not infrequent but may be less common when compared to other surgical specialties [6].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency services are some of the most important functions of any hospital and they cut across all specialties [6]. Urological emergencies are not infrequent but may be less common when compared to other surgical specialties [6]. Largely, they may not be immediately life threatening but require prompt and proper response to prevent long term complications [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation